2002
DOI: 10.1016/s1470-0328(02)01116-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of postpartum stress incontinence in primigravidae with increased bladder neck mobility: a randomised controlled trial of antenatal pelvic floor exercises

Abstract: Objective To test whether supervised pelvic floor exercises antenatally will reduce the incidence of postpartum stress incontinence in at-risk primigravidae with bladder neck mobility, ultrasonically proven. Design Single blind, randomised controlled trial.Setting Antenatal clinic in a UK NHS Trust Hospital.Sample Two hundred and sixty-eight primigravidae attending an antenatal clinic at approximately 20 weeks of gestation with bladder neck mobility, on standardised valsalva, of 5mm or more linear movement. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
228
0
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(234 citation statements)
references
References 10 publications
1
228
0
5
Order By: Relevance
“…A specific preventive effect of PFMT was shown in the studies by Reilly et al ,29 Gorbea Chávez et al 26 and in the subgroup of women with no previous UI at inclusion in the trials from Mørkved et al 28 and Stafne et al 23 No adverse effects of the interventions were reported. Sampselle et al 30 found that the short-term effect was not present at 1-year follow-up.…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…A specific preventive effect of PFMT was shown in the studies by Reilly et al ,29 Gorbea Chávez et al 26 and in the subgroup of women with no previous UI at inclusion in the trials from Mørkved et al 28 and Stafne et al 23 No adverse effects of the interventions were reported. Sampselle et al 30 found that the short-term effect was not present at 1-year follow-up.…”
Section: Resultsmentioning
confidence: 90%
“…Sampselle et al 30 found that the short-term effect was not present at 1-year follow-up. Eight years follow-up data from Reilly et al 's29 trial showed no significant difference in UI between the original intervention and control groups 31. Mørkved et al 32 reported that the percentage of continent women in the training group was similar at 3 months and 6 years’ follow-up, while the percentage of continent women in the control group had increased in the period, and the statistically significant differences between groups were no longer present.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations